1998
DOI: 10.1002/(sici)1096-9861(19980824)398:2<289::aid-cne9>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Vagal and spinal afferent innervation of the rat esophagus: A combined retrograde tracing and immunocytochemical study with special emphasis on calcium-binding proteins

Abstract: Vagal afferent neurons contain a variety of neurochemical markers and neuroactive substances, most of which are present also in dorsal root ganglion cells. To test for the suitability of the calcium-binding protein calretinin as a specific marker for vagal afferent fibers in the periphery, immunocytochemistry for this protein was combined with retrograde tracing. Nerve fibers in the rat esophagus, as well as vagal and spinal sensory neurons innervating the esophagus, were investigated for co-localization of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
68
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 66 publications
16
68
3
Order By: Relevance
“…Similar to observations made in the rat esophagus (Du¨tsch et al 1998;Kuramoto and Kuwano 1994), this study revealed that also the myenteric plexus of the guinea-pig esophagus harbours CB-ir neurons. In the cervical and thoracic regions of the esophagus, approximately 5% of all intrinsic neurons expressed CB, while no CB-positive neurons were present in the abdominal region.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to observations made in the rat esophagus (Du¨tsch et al 1998;Kuramoto and Kuwano 1994), this study revealed that also the myenteric plexus of the guinea-pig esophagus harbours CB-ir neurons. In the cervical and thoracic regions of the esophagus, approximately 5% of all intrinsic neurons expressed CB, while no CB-positive neurons were present in the abdominal region.…”
Section: Discussionsupporting
confidence: 89%
“…SP/VGLUT2 co-staining in varicose fibers could also be of spinal primary afferent origin. However, as most if not all afferent SP neurons contain CGRP (Dütsch et al 1998;Holzer 1988;Maggi 1995), and CGRP/ VGLUT2 fiber co-staining was never observed in our previous study (Raab and Neuhuber 2003), SP/VGLUT2 colocalization as observed in the present study was unlikely to be ascribed to spinal primary afferents.…”
Section: Vglut2-ir and Iglessupporting
confidence: 51%
“…The colocalization mismatch of VGLUT2-ir and calretinin-ir or tracer, respectively, found in our previous study (Raab and Neuhuber 2003), could therefore best be explained by a less complete demonstration of IGLEs by both anterograde tracing and calretinin-ir. Thus, VGLUT2-ir may be used as a selective and even more efficient and reliable marker than calretinin (Dütsch et al 1998) and anterograde tracing for IGLEs in the esophagus of rat and mouse, respectively, and may be used as an alternative to P2X2 which was shown to label IGLEs in both mouse (Castelucci et al 2003) and rat (Wang and Neuhuber 2003).…”
Section: Vglut2-ir and Iglesmentioning
confidence: 99%
“…7b). In all myenteric ganglia examined (n = 12) no CGRP-ir could be detected within neuronal perikarya resembling the pattern previously described (Dütsch et al 1998;Sang and Young 1998). Analysis in merged two-channel single optical sections revealed no spots of colocalization within the same proWle but close apposition of P2X 3 -iry and CGRP-ir varicosities (yellow) at the site of contact, indicating proximity beyond the resolution of the confocal technique (arrows in Fig.…”
Section: P2x 3 and Thsupporting
confidence: 74%